Knowledge, Self-Efficacy, and Performance of Patient Education in Heart Failure Among Nurses in Indonesia - Chen, Hsing-Mei; Djunizar Djamaludin (STIKep PPNI Jawa Barat, 2021)
Background: Nurses play a vital role in educating Heart Failure (HF) patients about the disease, and should be knowledgeable about what they teach. Likewise, a nurse should believe in his or her own capability to effectively give a health education based on his or her knowledge about HF management, and this known as self-efficacy. Objectives: The purpose of this study was to examine the relationships among HF knowledge, self-efficacy, and performance as well as determinants of performance in HF education among nurses who took care of patients with cardiac diseases. Methods: A cross sectional study design with convenience sampling was employed and 135 participants were recruited from five units (male and female medical ward, cardiac ward, ICU, ICCU, and VIP unit) at a general hospital in Bandar Lampung, Indonesia. Four instruments were used, including the Nurses’ Knowledge of Heart Failure Education Principles questionnaire, Nurse Self-Efficacy Scale, and HF Knowledge Education Scale of Nursing Performance. Data were analyses using, Mann-Whitney U and Kruskal-Wallis test were used to examine association between mean scores on the study variables. Results: A significant relationship was found between nurses’ self-efficacy and performance of HF education (r=0.59, p= 0.000), but the relationship between nurses’ knowledge and performance of HF education was not significant (r= -0.33, p= 0.01). Conclusions: This study found that the nurses in general hospital in Lampung, Indonesia, may not be sufficiently knowledgeable about HF education principles. Nevertheless, the nurses mostly had high self-efficacy as well as good performance with regard to HF education.